Designing EU Supply Chain Regulation - Gabriel Felbermayr; Klaus S. Friesenbichler; Markus Gerschberger; Peter Klimek; Birgit Meyer (Intereconomics, 2024)
The EU Directive on Corporate Sustainable Due Diligence has sparked fierce debate about the regulation of supply chains. The directive's objectives are aligned with European values. However, it raises concerns that the compliance costs of social and environmental regulations may be privatised in complex supply networks, particularly in third countries with weak enforcement mechanisms. This paper suggests options to make the directive more effective and efficient. It suggests excluding countries with sufficient regulatory systems and focusing only on supplier-buyer relationships instead of the entire network. Public agencies should set harmonised regulatory standards, interpret the regulations and organise a private certification scheme in which certification companies assume liabilities. The proposed system resembles the market for financial auditors.
Keywords: F13; F18; J80; 330; Supply chain; Regulation; EU states; Lieferkette; Regulierung; EU-Staaten